2016
DOI: 10.7899/jce-15-8
|View full text |Cite
|
Sign up to set email alerts
|

Learning spinal manipulation: A best-evidence synthesis of teaching methods*

Abstract: Objective: The purpose of this study was to evaluate the effectiveness of different reported methods used to teach spinal manipulative therapy to chiropractic students. Methods: For this best-evidence literature synthesis, 5 electronic databases were searched from 1900 to 2015. Eligible studies were critically appraised using the criteria of the Scottish Intercollegiate Guidelines Network. Scientifically admissible studies were synthesized following best-evidence synthesis principles. Results: Twenty articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…7,8 Many of these principles have now been investigated in the context of SM learning, and relevant studies confirmed that SM learning follows these principles. 9 Indeed, it has been shown that SM skill acquisition is gradually acquired through the teaching curriculum, 10,11 that sequencing of theory and laboratory exercises is important, 12 that augmented feedback is valuable in SM skill development, [13][14][15] and that transfer capability assessments should be considered in SM training. 16 To our knowledge, benefits of task-induced variability during practice of accuracy and consistency have not been investigated in the context of SM learning.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Many of these principles have now been investigated in the context of SM learning, and relevant studies confirmed that SM learning follows these principles. 9 Indeed, it has been shown that SM skill acquisition is gradually acquired through the teaching curriculum, 10,11 that sequencing of theory and laboratory exercises is important, 12 that augmented feedback is valuable in SM skill development, [13][14][15] and that transfer capability assessments should be considered in SM training. 16 To our knowledge, benefits of task-induced variability during practice of accuracy and consistency have not been investigated in the context of SM learning.…”
Section: Introductionmentioning
confidence: 99%
“…5 Research is available on effective strategies to enhance teaching and learning of SM. 6 These strategies have included changing the learning structure; utilizing imme-diate feedback tools, such as force plates or specially designed tools; or utilizing mannequins for practice. 6 Recently, there has been work done examining the effect of utilizing a mannequin for cervical SM practice, which demonstrated positive effects in students' subjective scoring of cervical SM skills.…”
Section: Introductionmentioning
confidence: 99%
“…6 These strategies have included changing the learning structure; utilizing imme-diate feedback tools, such as force plates or specially designed tools; or utilizing mannequins for practice. 6 Recently, there has been work done examining the effect of utilizing a mannequin for cervical SM practice, which demonstrated positive effects in students' subjective scoring of cervical SM skills. 7,8 However, this did not include any examination of effects on a learners' objective outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…1 HVLA-SM training traditionally has begun with learning theoretical concepts before moving to motor skill practice with qualitative instructor feedback. 2,3 Strategies used to provide feedback include partial practice, which includes doctor-patient positioning without a manipulative thrust, and complete practice, which includes delivering a manipulative thrust. [4][5][6] Students participating in complete practice are able to deliver HVLA-SM thrusts more like those of experienced clinicians when comparing rate of force production.…”
Section: Introductionmentioning
confidence: 99%
“…Complete HVLA-SM practice can be accomplished with force-sensing technology incorporated into hand-interface devices or platform systems measuring thrust characteristics delivered to devices, humans, or mannequins functioning as simulated patients. [2][3][4] Using mannequins removes injury risk to patients 7,8 and provides additional training components compared to devices alone. Other potential benefits of using mannequins and force-sensing equipment include faster motor skill development, likely due to the greater potential for repeated practice, 5,9 and higher student confidence 4 and satisfaction.…”
Section: Introductionmentioning
confidence: 99%